Class politics and migrants: collective action among new migrant workers in Britain - Però, Davide (Sage, 2014)
This article addresses issues of class-based collective action. Through an ethnographic case study examining migrant workers’ political engagements, the article discusses the current relevance of class politics and the role that culture, identity and intersectionality seem to play in it. By focusing on the collective political practices observed among Latin American migrant workers in London, it seeks to contribute to the ‘new sociology of class’, an emerging strand within the discipline which has begun to explore the identity and cultural dimension of class. In particular, it aims to broaden the scope of this strand beyond the individual so as to include the collective and contentious dimension of class and to enhance its sensitivity to new migrants and to the ‘super-diverse’ nature of contemporary society.